PENGARUH TIME BUDGET PRESSURE DAN LOCUS OF CONTROL TERHADAP KINERJA AUDITOR DINAS INSPEKTORAT: PENGARUH TIME BUDGET PRESSURE DAN LOCUS OF CONTROL TERHADAP KINERJA AUDITOR DINAS INSPEKTORAT - Sari Kawuryan; Nurul Wahidatun Nisa'; Makhshushi Zakiyah (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2022)
This study was conducted to determine whether there is an effect of time budget pressure and locus of control on the auditor's performance. The study was conducted by conducting a literature review involving several previous studies which also examined time budget pressure and locus of control on auditor performance in various different objects. Based on the literature review conducted, it can be concluded that time budget pressure has a significant effect on the performance of the auditor, meaning that the level of time pressure given to the auditor works has an effect on his performance. Likewise, the locus of control variable has a positive and significant effect on the auditor's performance, because it tends to make an auditor work more thoroughly, and can also be the causes of success or failure in carrying out his work.